Medico-Sanitary and Parasitological Aspects of Rock Pigeon Ecology (Columba livia) - A. V. Gorbunov; N. S. Nefedova; M. A. Shmidt (Проблемы особо опасных инфекций, 2012)
Collected are the data on sanitary-hygienic and parasitological aspects of rock pigeon vital activity in Saratov. Distinguished are the types of pigeon exterior pathologies, their character and frequency of occurrence. Synanthropic population and nests of the birds are searched for the presence of helminthes and ectoparasites. Identified is the role of nesting sites, located in attics of residential buildings, in sanitary and epidemiological situation of the city settlement zone.